Rynek ubezpieczeń gospodarczych jako element rynku finansowego - Przybytniowski, Jarosław (Przegląd Prawno-Ekonomiczny, 2007)
Streszczenie dostępne wyłącznie w języku angielskim: The integrating of subjects’ activity occurring in economy is essential task of financial system. The countries adherent to European Union posses different Solutions in range of supervision over financial markets. In Polish financial system exists the integrated form of supervision, which aim is assurance of correct working of financial system, its stability, safety as well as transparency and confidence to market. Insurances are one of the elements of financial market. On level of world market or regional in continent scale has influence the most developed inland markets. The unification of EU law permitted on creating the standards, which in spite of large differentiation of intemal markets of the member States, integrated with themselves. The worldwide tendencies show on consolidation of insurance markets and the stint of number of subjects operating on inland markets. Among the countries adherent to European Union before 1st May 2004 the premium account from insurances from Sector I tops the fee from Section II. Opposite situation takes place in case of new members of European Union. Such State can testify about differences in way of approach to essence and usefulness of insurances. The population of hitherto exist members of EU treats the insurance as form of future protection. For new members the most important is the compensation of losses function.